Best-shot network games with continuous action space. Issue 3 (September 2019) - Ghosh, Papiya; Kundu, Rajendra P.
Abstract: This paper presents a model of public good provision in networks where the level of public good that an agent has access to depends on the maximum of contributions by the agents in her neighbourhood. Our analysis shows that the game always has an equilibrium in pure strategies and all equilibria are specialised and stable. Welfare analysis shows that formation of new links in a prevailing network may not always be useful.